Pengaruh Kompetensi Kerja Terhadap Kinerja Pegawai Pada Dinas Komunikasi Informatika Dan Komunikasi Kabupaten Bima - Adesan Putra; Jaenab Jaenab (JURNAL RISET MANAJEMEN (JURMA), 2023)
This research aims to examine the influence of work competency on employee performance at the Bima Regency Informatics and Communication Service. This research is a type of associative research. The population used in the research was all employees at the Bima Regency Informatics and Communication Service, totaling 65 employees. The sample technique used was purposive sampling, so the sample in this study was 40 employees with ASN status. The instrument used in data collection was a questionnaire which would be given a score based on a Likert scale. This research uses a simple linear regression analysis method which involves one dependent variable and one independent variable. The results of this research show that work competency has a positive and significant effect on employee performance at the Bima Regency Informatics and Communication Service.